2012
DOI: 10.5301/ejo.5000118
|View full text |Cite
|
Sign up to set email alerts
|

Changes of serum VEGF concentration after intravitreal injection of Avastin in treatment of diabetic retinopathy

Abstract: Intravitreal injections of anti-VEGF drugs have an effect on decreasing systemic VEGF values. Rhythm of changes in serum VEGF concentrations and lowest detected concentration on the seventh postinjection day are according to pharmacokinetics of Avastin in serum and vitreous, reported by similar studies. The small number of patients involved in this pilot study implicates the need for further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…[28][29][30][31] This clearly demonstrates that intravitreally injected IgG can cross the blood-retina barrier. In contrast, systemic plasma concentrations of VEGF were not affected by intravitreal ranibizumab (an anti-VEGF Fab fragment, lacking an Fc domain).…”
Section: Discussionmentioning
confidence: 75%
“…[28][29][30][31] This clearly demonstrates that intravitreally injected IgG can cross the blood-retina barrier. In contrast, systemic plasma concentrations of VEGF were not affected by intravitreal ranibizumab (an anti-VEGF Fab fragment, lacking an Fc domain).…”
Section: Discussionmentioning
confidence: 75%
“…Dysregulation of VEGF expression within the glomeruli has been associated with a wide range of renal diseases that may occur within weeks to months after intravitreal administration of VEGF inhibitors [14], [27]. The dose of anti-VEGF agents used in ophthalmology is minute compared with that used intravenously, but there is evidence of systemic absorption and diffuse inhibition of VEGF [14], [17], [38], [39]. Pelle et al ., reported a non diabetic patient with normal kidney function who developed kidney toxicity after four injections of ranibizumab for the treatment of age-related macular degeneration [14].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that there is a decline in inflammatory and angiogenic markers namely IL-6 and VEGF with the onset of proliferative diabetic retinopathy changes [12]. The reduction in angiogenic factors with worsening of retinopathy may explain the role of VEGF in initiating the proliferative changes and systemic worsening [13]. However, the final end point is secondary to the sequel arising out of the fibrovascular proliferation.…”
Section: Discussionmentioning
confidence: 99%